Contextual Teaching and Learning in Arabic as a Foreign Language: A Classroom-Based Case Study in Indonesia - Nabila Nashfati; Salamuddin (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) approach in Arabic language instruction for seventh-grade students at MTs Ar-Ridho Medan, and to analyze the supporting and inhibiting factors during its implementation. Employing a qualitative approach with a case study design, the research explores pedagogical practices in authentic classroom settings through observation, semi-structured interviews, and documentation. The findings reveal that the teacher successfully integrated all seven core components of CTL (constructivism, inquiry, learning community, modeling, reflection, meaningful learning, and authentic assessment) into classroom practice. Students demonstrated high enthusiasm, active participation, and a contextual understanding of the material. Nevertheless, challenges such as limited instructional time, insufficient learning facilities, and diverse student characteristics require strategic management. This study offers both practical and theoretical contributions to the development of more meaningful Arabic language instruction models in Islamic schools.